Fiscal policy and TFP in the OECD: Measuring direct and indirect effects - Gerdie Everaert; Freddy Heylen; Ruben Schoonackers (National Bank of Belgium, 2014)
This paper analyzes the direct and indirect effects of fiscal policy on total factor productivity (TFP) in a panel of OECD countries over the period 1970-2012. Our contribution is twofold. First, when estimating the impact of fiscal policy on TFP from a production function approach, we identify the worldwide available level of technology by exploiting the observed strong cross-sectional dependence between countries instead of using ad hoc proxies for technology. Second, next to direct effects, we allow for indirect effects of fiscal policy by modelling the access of countries to worldwide available technology as a function of fiscal policy and other variables. Empirically, we propose and implement a non-linear version of the Common Correlated Effects Pooled (CCEP) estimator of Pesaran (2006). The estimation results show that through the direct channel budget deficits harm TFP. A shift towards productive expenditures has a strong positive impact on TFP, whereas a shift towards social transfers reduces TFP. Through the indirect channel, significant positive effects on a country's access to global technology come from reducing the statutory corporate tax rate and from reducing barriers to trade.
Keywords: C31; C33; E62; O38; 330; Fiscal policy; TFP; Unobserved Common Factors; Panel Data; Finanzpolitik; Produktivitätsentwicklung; Vergleich; Panel; OECD-Staaten